2021
DOI: 10.1371/journal.pone.0256086
|View full text |Cite
|
Sign up to set email alerts
|

What it takes to save lives: An assessment of water, sanitation, and hygiene facilities in temporary COVID-19 isolation and treatment centers of Southern Ethiopia: A mixed-methods evaluation

Abstract: Background Quality water, sanitation, and hygiene facilities act as barricades to the transmission of COVID-19 in health care facilities. These facilities ought to also be available, accessible, and functional in temporary treatment centers. Despite numerous studies on health care facilities, however, there is limited information on the status of WASH facilities in such centers. Methods The assessment of health care facilities for the COVID-19 response checklist and key informant interviews, were used for da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…WHO recommends people with suspected or confirmed SARS-CoV-2 should be provided a separate toilet, and if not possible, certain toilets should be designated as solely for the shared use of COVID-19 patients and not used by non-COVID-19 patients [20]. In this study, 56% of the HCFs had separate toilets for males and females, which was lower than the study finding in Ethiopia 94.3% [44]. This finding also revealed that 7.1% of HCFs had low cleanliness of the latrine, which may be associated with the absence of a functional lock on the latrine door and lack of lighting, frequency of cleaning, and the behavior of clients in utilizing of latrines.…”
Section: Plos Onecontrasting
confidence: 66%
See 1 more Smart Citation
“…WHO recommends people with suspected or confirmed SARS-CoV-2 should be provided a separate toilet, and if not possible, certain toilets should be designated as solely for the shared use of COVID-19 patients and not used by non-COVID-19 patients [20]. In this study, 56% of the HCFs had separate toilets for males and females, which was lower than the study finding in Ethiopia 94.3% [44]. This finding also revealed that 7.1% of HCFs had low cleanliness of the latrine, which may be associated with the absence of a functional lock on the latrine door and lack of lighting, frequency of cleaning, and the behavior of clients in utilizing of latrines.…”
Section: Plos Onecontrasting
confidence: 66%
“…According to the WHO standard, functional hand hygiene facilities should be available at all critical points of the HCFs [7]. Less than a quarter (21.4%) of the HCFs had functional handwashing facilities (with water and soap) both in latrines and at point of care, which was lower than the studies conducted in Africa (28%) [41], Zimbabwe (30%) (26), LMICs [12], sub-Saharan Africa (67%) [8], Rwanda (32%) [40], Nigeria (66%), Rwanda (65%), Zimbabwe (58%) [7] and Ethiopia (74.28%) [44] but higher than Niger (4%) [7].…”
Section: Plos Onementioning
confidence: 90%
“…Inadequate access to PPE (e.g., hygiene materials) and lack of WASH infrastructure (e.g. running water for handwashing) presented major barriers to preventative behaviors in healthcare facilities and in the community [ 13 , 16 , 22 ]. Community participants mentioned that the handwashing stations in public places often lacked water and cleansing agents.…”
Section: Discussionmentioning
confidence: 99%
“…In Zimbabwe and the Democratic Republic of the Congo (DRC), common barriers to compliance with preventative measures included living and working in crowded areas, local understandings of COVID-19, and misinformation through social media [ 15 , 16 ]. Previous studies in the sub-Saharan Africa region have recommended tailoring health communication to the local context [ 17 , 18 , 19 ], prioritizing trust-building between communities and the Ministries of Health (MoH) [ 20 , 21 ], and ensuring adequate provision of hygiene and PPE materials for effective COVID-19 response programs [ 15 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Covid-19 pandemic, which began in Wuhan, China, in December 2019, has had an impact on the economy. In this context, it is recorded that about 82.85% of businesses in Indonesia experienced a decrease in revenue during the pandemic [1]. This decrease in revenue occurred because many companies were forced to temporarily halt their business operations, and the decline in consumer demand also had an impact [2].…”
Section: Introductionmentioning
confidence: 99%